CEO contractual protection and managerial short-termism - CHEN, Xia (Institutional Knowledge at Singapore Management University, 2013)
How to address managerial short-termism has been an important issue for companies, regulators, and researchers. In this paper we examine the impact of CEO contractual protection, in the form of employment agreement and severance pay agreement, on managerial short-termism. We find that firms with CEO contractual protection are less likely to cut R&D expenditures to avoid earnings decreases. The effect is both statistically and economically significant. We further find that the effect of CEO contractual protection is stronger in cases where CEOs have stronger incentives to engage in myopic behavior, either due to job security concerns or due to short investment horizon of investors, and in cases where alternative monitoring mechanisms are weaker.